Expertos que diseñan el dinero: el caso de los programas de transferencias monetarias - Hornes, Martín Eduardo (El Colegio de México, 2019)
This article analyzes the interpretations about money that build expert knowledge in social programs of cash transfers. It is based on a qualitative investigation of in-depth interviews with relevant experts in the field of social policies of the Argentine Republic, between 2015 and 2016. The results show the need to build a perspective of analysis that not only asks for specialized knowledge that expert knowledge uses to refer to money transferred to the poor sectors, but also challenges such interpretations incorporating reflections from the sociology of money in the popular world.